Approaches to improving the effectiveness of risk-management of business entities - A. V. Palbin (Путеводитель предпринимателя, 2020)
The article considers issues of efficiency ofactivity of business entities in the light of the implementation and application of risk-management in the management of economic entities. Defined performance criteria and evaluating the implementation of the riskmanagement process of business entities. Identified a number of difficulties that complicate the analysis of the effectiveness of risk- management, including, in particular, a situation when the risk event in respect of which was held protivogribkovye of the event, have not materialized.